315 "I JUST GOT ON WITH IT": EXPLORING THE PATIENT EXPERIENCE OF STROKE REHABILITATION DURING THE COVID-19 PANDEMIC. (25th October 2022) - Madden, R; Galvin, R; Horgan, F
Abstract: Background: There are emerging studies examining the pandemic experiences for older adults and healthcare staff, however the impact of COVID-19 on stroke rehabilitation has yet to be examined. Family involvement and social support is central to adjustment during stroke rehabilitation and this was impacted by the pandemic and its restrictions. The aim of this study was to explore first-person lived experiences of stroke rehabilitation in an Irish rehabilitation hospital setting during the COVID-19 pandemic and understand how COVID-19 restrictions impacted on patients' experiences of stroke rehabilitation. Methods: A qualitative descriptive design was implemented with a purposive sample of stroke survivors, who had undergone stroke rehabilitation between January – December 2021 at an Irish post-acute rehabilitation hospital. Semi-structured interviews were used as the primary data collection method and were audio-recorded and transcribed verbatim. Data were analysed using Braun & Clarke's (2018) six-step approach and external data validator was used for inter-coder reliability. Results: Eight stroke survivors were interviewed (male n=5, female n=3). Four main themes were identified: (i) Resilience and coping, (ii) Feeling supported along the journey, (iii) The pinch of COVID-19, (iv) Adjustment and moving on. The stroke survivors' resilience was an important recurring theme throughout the analysis. A sense of feeling supported by hospital staff and peers was also prominent. The impact of COVID-19 restrictions was felt by all participants, however, resilience, support from hospital staff and peers were the strongest recurring themes. Conclusion: COVID-19 restrictions had an impact on the stroke rehabilitation experience, however, stroke survivors felt well-supported and showed resilience in spite of this. To the best of the researchers' knowledge, this is the first study which examines first-person accounts of stroke survivors during the COVID-19 pandemic, thus offering a unique perspective on the experiences of this cohort, who were hospitalised during this time.